Discussion on design aspects for free-space optical communication terminals. - Epple, Bernhard (IEEE Communications magazine)
Free-space optical communications is an emerging solution to increase link capacity of nondetectable links to multi gigabits per second. FSO is widely believed as to overcome radio frequency spectrum and data rate limitations. However, one of the biggest challenges facing FSO deployment is its optical signal propagation in different atmospheric conditions. This effect causes variable link degradation due to variable attenuation and fading. Atmospheric turbulence produces temporary pockets of air with slightly different indices of refraction. Therefore the laser beam phase-front varies randomly, producing intensity fluctuation. One further key challenge with FSO systems is maintaining transceiver alignment. Using highly directional and narrow beams of light, variable mispointing of the transmit beam, and tracking errors of the receiver will generate additional signal fading. In this article terminal design aspects are discussed, and problems that occur when building FSO terminals are highlighted.